Investigating Learners’ Perceptions of TikTok for Vocabulary Development: Acquisition, Motivation, and Barriers - Muhammad Hafizh Rozan; Semi Sukarni; Sri Widodo (Journal of Education Research, 2026)
The rapid development of digital technology has transformed language learning by providing students with more interactive and engaging learning media. Among various social media platforms, TikTok has gained increasing attention as a potential educational tool due to its short-form video content and widespread popularity among adolescents. This study aimed to examine students' perceptions of the use of TikTok in vocabulary learning. Specifically, it investigated the extent to which TikTok contributes to vocabulary acquisition and retention, influences students' learning motivation, and identifies the challenges encountered when using the platform as a learning medium. A descriptive quantitative research design was employed involving 30 eleventh-grade students at SMA Negeri 7 Purworejo, Indonesia. Data were collected using a Likert-scale questionnaire distributed through Google Forms and analyzed using descriptive statistics, including mean scores and percentages. The findings revealed that students perceived TikTok as an effective medium for vocabulary learning because it enhanced their motivation and learning engagement compared with conventional teaching methods. However, several challenges were identified, including distractions from entertainment content and difficulties in finding relevant educational materials.